The evertree - Lu, Marie, 1984- (New York, NY : Scholastic Inc., 2015)
Conor, Abeke, Meilin, and Rollan have journeyed across Erdas, racing to stop a merciless foe. Now that journey is about to end. They must reach a place forgotten by time and face off against an ancient enemy breaking free from his prison. They have just one chance to stop him -- or the whole world will shatter.
Keywords: Human-animal relationships -- Juvenile fiction; Good and evil -- Juvenile fiction; Shapeshifting -- Juvenile fiction; Fantasy; Good and evil; Human-animal relationships; Shapeshifting; Fiction; Juvenile works; Fantasy fiction